Association of Helicobacter Pylori with Peptic Ulcer Perforation - Agrawal, Sunit; Thakur, D; Kafle, P; Koirala, A; Sanjana, R K; Kumar, S; Patowary, B N (Journal of BP Koirala Institute of Health Sciences, 2019)
Background: Helicobacter pylori is found in more than 90% cases of peptic ulcer. This study examines the possibility of association of Helicobacter pylori in perforated peptic ulcer disease and its relation to persisting ulcer as well as the influence of other risk factors; namely: smoking, alcohol, current non-steroidal anti inflammatory drugs (NSAIDs) and steroid use.Materials and Methods: In this prospective study, total of 50 cases of peptic ulcer perforation admitted in College of Medical Sciences and Teaching Hospital, Bharatpur, Nepal were selected on the basis of the non-probability (purposive) sampling method. All patients who presented with suspected peptic ulcer perforation were included in the study and the perforations were repaired by Modified Graham’s Patch and were given triple therapy postoperatively. The age, sex, incidence, mode of presentation, precipitating factors, association with the risk factors and postoperative complications were all evaluated and compared.Results: Of 50 patients studied, the age ranged from 17 to 75 years, mean age being 40.1 years with the peak incidence in the 3rd and 5th decades of life showing a male dominance (92%). H. pylori was seen in ulcer edge biopsy in 29 patients (58%). Most common clinical presentation was pain abdomen, the most common signs of perforation were tenderness, rebound tenderness and absent bowel sounds. The mean duration of stay in hospital in H. pylori positive patients was 12.07±8.15 days as compared with 11.1±5.12 days in H. pylori negative patients. The incidence of peptic ulcer perforation was higher in the patients consuming alcohol (64%) than smokers (48%), followed by NSAIDs user(22%). 20% of the patients with delayed presentation developed complications postoperatively. Perforated peptic ulcer was repaired by Modified Graham’s Patch Repair, followed by anti H. pylori therapy in all of them.Conclusion: Peptic ulcer perforation is quite common among the patients with peptic ulcer disease with history of chronic smoking, alcoholism and analgesic intake, more commonly in males. There is association of H. pylori in 58% of patients with peptic ulcer perforation.